Role of Laser Doppler for the Evaluation of Pedal Microcirculatory Function in Diabetic Neuropathy Patients. (January 2016) - Park, Hyung Sub; Yun, Han Mi; Jung, In Mok; Lee, Taeseung
Abstract: Objective: We evaluated whether LD can detect alterations in skin microcirculatory flow in type II diabetic neuropathy patients and determined which parameters were most predictive. Methods: A prospective analysis was performed for three groups with presumed varying degrees of microvascular dysfunction: diabetics with neuropathy (DMN, n = 20), diabetics without microangiopathic complications (DM, n = 20), and healthy controls ( n = 16). LD was performed under strictly controlled protocols with provocation, consisting of vasoconstrictive (valsalva, postural) and vasodilative tests (PORH, LTH). Results: There was an overall decrease in LD values in response to both vasoconstrictive and vasodilative provocations in DMN patients compared to DM and control groups. Statistically significant parameters were as follows: valsalva, PORH and LTH between DMN and control; valsalva only between DMN and DM; and PORH and LTH between DM and control. ROC curve analysis showed that Valsalva was the most accurate parameter in DMN patients. Conclusions: LD could consistently detect differences in microcirculatory flow between the three study groups consisting of gradually more severe microvascular dysfunction. The Valsalva parameter was the most accurate in detecting established microvascular dysfunction, whereas PORH and LTH may have a possible role for detection of early microvascular impairment.